STUDI PENDAHULUAN MASERASI COUPLING ELEKTROSINTESIS DALAM MENGEKSTRAKSI NIKOTIN YANG TERKANDUNG DALAM PUNTUNG ROKOK DAN ANALISA MENGGUNAKAN SPEKTROSKOPI UV-VIS - Muhammad Taufik; Rid Wanto; Siti Rahmah Cibro; Desi Ardilla; Mariany Razali; Dafni Mawar Tarigan (PROSIDING SEMINAR KIMIA, 2017)
This paper is a preliminary research in the application of electrosynthesis method in extracting the sample. The maceration process of extraction is one of the simplest ways of extracting nicotine in a preparation. The extraction process can be accelerated by electrochemical principle. The method developed is maceration coupling electrosynthetise in analyzing nicotine contained in cigarette butts. Descriptive method developed in the process of nicotine maseration on filter cigarettes and non-filter cigarettes using ethanol solvents. The experimental method was developed in maceration process and maceration coupling electrosynthesis with variation of time respectively 5, 10, 15, 20, 25 minutes. The best results were obtained on non-filter cigarettes using maceration coupling electrosynthesis at 20 and 25 minutes with qualitative results with cyanogen bromide marked by abundant yellow (+++). The analysis continued using UV-Vis spectrophotometry method and obtained the best sample concentration on non-filter cigarette method of maceration coupling electrosynthesis at 15 minute ( 0,01003 ppm). Keywords: nicotine, filter cigarettes, non-filter cigarettes, electrosynthesis, UV-Vis spectrophotometry